PROSPECTS FOR THE DEVELOPMENT OF PEACE AND STABILITY IN THE SOUTHERN CAUCASUS - DEM RAG, Yelda (CENTRAL ASIA AND THE CAUCASUS, 2006)
The dramatic change that took place after the end of the Cold War has brought conceptual changes in the literature of International Relations. Security and stability are two such concepts which were affected on a major scale from this change.1 In this period, new elements like regional and ethnic conflicts, human rights, religious fundamentalism, international terrorism, economic problems, illegal trafficking of drugs and weapons gained threat status. The South Caucasian region represents one of the most diverse and conflict-ridden regions in the world. It includes the three former Sovietstates of Armenia, Azerbaijan and Georgia, as well as numerous ethnic minorities and small nations within these states. Three kinds of rival-ries have been observed in the region since their independence: Firstly, between the regional states like Turkey, Iran and Russia, secondly between South Caucasian states themselves and thirdly between nations within the states.2 These rival-ries have become extremely complex, especially since the involvement of the U.S. from the mid-1990s. Each of these states, while trying to influ-ence the dynamics of regional developments, de-veloped policies based on various historical, eco-nomic, ethno-linguistic and cultural factors. How-ever, as mentioned before, the main factors that allowed external powers to get a foothold in the region were the continuing regional conflicts, on the one hand, and energy resources, on the oth-er.3 The conflict of political and economic inter-ests among these powers prevents a solution to the instability in the region. The first of the ethnic conflicts which are the main reason for this instability occurred in the Armenian populated enclave Nagorno-Karabakh located within the territorial boundaries of Azerbaijan. The two other conflicts occurred in Georgia, between the Georgian central authorities of Tbilisi and the autonomous regions of Abkhazia and South Ossetia. In all the three cases, cease-fire agreements were reached without final settlements.